Polyvinyl alcohol fiber reinforced cement board and manufacturing method thereof
Through copolymerization reaction and surface modification, cross-linking curing treatment of PVA fiber and cement materials was prepared, and combined with foaming treatment, polyvinyl alcohol fiber reinforced cement boards were prepared, which solved the problems of complex process and poor weather resistance of existing cement boards, and achieved high strength, high toughness and high weather resistance cement boards.
Patent Information
- Application Number
- CN202510265570.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-07
AI Technical Summary
The existing fiber-reinforced cement boards have complex production processes and poor weather resistance, making it difficult to meet the multi-faceted demands of the construction industry for cement material performance.
The first PVA fiber is prepared by copolymerization and surface modification and mixing with high alumina cement and other materials to prepare a reinforced outer layer, and the second PVA fiber is prepared by cross-linking and modification and mixing with silicate cement and other materials to prepare a fiber-modified intermediate layer, and foaming is carried out on the surface of the fiber-modified intermediate layer to prepare a foamed inner layer to form a polyvinyl alcohol fiber reinforced cement board.
It improves the mechanical strength, fire resistance and aging resistance of cement boards, reduces process difficulty, enhances the composite effect of the plate layer, and extends the service life.
Smart Images

Figure CN119773030A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wall materials and relates to a polyvinyl alcohol fiber reinforced cement board and a manufacturing method thereof. Background Art
[0002] As a traditional material in the construction field, cement materials have been widely used due to their good performance. With the development of the construction industry, the performance requirements for cement are also increasing. The strength and functionality of traditional cement materials have gradually failed to meet the current multi-faceted needs for cement. Therefore, various composite cement materials or reinforced cement materials have emerged. Among them, fiber-reinforced cement, as an important branch of composite cement materials, has the characteristics of high strength and high toughness, and is attracting more and more attention.
[0003] Compared with traditional cement materials, fiber-reinforced cement materials have higher strength and lower density, and can be endowed with a variety of unique functions based on the different characteristics of the fibers, greatly expanding the application scope of cement materials. In recent years, people have made many advances in the related research fields of fiber cement materials.
[0004] For example, Chinese patent CN115403337B proposes a negative carbon fiber cement board and a preparation method thereof, by preparing a fiber suspension, mixing with additives to prepare a slab, and obtaining a negative carbon fiber cement board by dehydration, curing and other treatments, which can avoid cement board stratification and other phenomena, and has low energy consumption and good preparation effect. The problem with this invention is that the functionality of a single-layer cement board is relatively single. Chinese patent CN114230263B proposes a fiber cement board and a preparation method thereof, by mixing modified nano hollow microspheres and cement glue, reinforcing fibers and other materials to prepare a super-hydrophobic fiber cement board, which has significant fire retardant properties under the condition of good mechanical properties. The problem with this invention is that the preparation process has strict requirements on reaction conditions, and the process stability is difficult to guarantee. Chinese patent CN112390597B proposes a preparation method for a composite plant fiber cement board, which modifies plant straw fibers and fly ash fibers, etc., and improves the mechanical properties of the fiber cement board. The problem with this invention is that the bonding strength between plant fibers and cement will gradually weaken, making it difficult to achieve high weather resistance.
[0005] At present, the existing fiber-reinforced cement board has complex manufacturing process and poor weather resistance, which are still major problems facing the industry.
[0006] Therefore, a polyvinyl alcohol fiber reinforced cement board and a manufacturing method thereof are proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a polyvinyl alcohol fiber reinforced cement board and a method for making the same. The present invention prepares a first PVA fiber by copolymerization and surface modification, and mixes it with a first cement raw material to prepare a reinforced outer layer; prepares a second PVA fiber by crosslinking modification, and crosslinks and solidifies it with the second cement raw material on the surface of the reinforced outer layer to prepare a fiber-modified middle layer; mixes PVA resin with a foaming agent and a reinforcing agent, and foams the surface of the fiber-modified middle layer to prepare a foamed inner layer; the reinforced outer layer, the fiber-modified middle layer and the foamed inner layer sequentially form a polyvinyl alcohol fiber reinforced cement board.
[0008] To achieve the above object, the present invention provides the following technical solutions: A method for manufacturing a polyvinyl alcohol fiber reinforced cement board comprises the following steps: Preparation of the first PVA fiber by copolymerization and surface modification: 100 parts of vinyl alcohol, 30 parts of vinyl chloride and 2 parts of dioctyl phthalate are dissolved in tetrahydrofuran under a pressure of 5 atm, 1 part of azobisisobutyronitrile is added, the temperature is raised to 60-80°C, and the reaction is stirred at 200 rpm for 4-5 hours. The solution is extruded through a spinneret to obtain a copolymer fiber, which is washed with ethanol to obtain a first PVA precursor; the first PVA precursor is heated to 120°C and maintained for 3 hours, and then cooled to 25°C to obtain a first PVA fiber.
[0009] The first PVA fiber and the first cement raw material are preliminarily mixed and cured in a mold to obtain a reinforced outer layer.
[0010] Preparation of the second PVA fiber by cross-linking modification: 100 parts of PVA fibers were immersed in water and swelled at 40°C for 2 hours to obtain swollen PVA fibers; 100 parts of swollen PVA fibers were placed in 4wt% glutaraldehyde solution, the pH was adjusted to 3-4, stirred at 60°C at 300rpm for 3.5 hours, and washed and dried to obtain a second PVA fiber.
[0011] The second PVA fiber and the second cement raw material are stirred and mixed, and the fiber-modified middle layer is obtained after the surface of the reinforced outer layer is cross-linked and cured.
[0012] The PVA resin is mixed with a reinforcing agent and a foaming agent, and then foaming treatment is performed on the surface of the fiber-modified middle layer to obtain a foamed inner layer.
[0013] The reinforced outer layer, the fiber-modified middle layer and the foamed inner layer are sequentially composed of the polyvinyl alcohol fiber reinforced cement board.
[0014] Preferably, the first cement raw material includes: high alumina cement, sulphoalumina cement and triphenyl phosphate; wherein the addition ratio of high alumina cement, sulphoalumina cement and triphenyl phosphate is 30:70:1.
[0015] Preferably, the second cement raw material comprises: silicate cement, sulphoaluminum cement and polyethylene glycol; wherein the addition ratio of silicate cement, sulphoaluminum cement and polyethylene glycol is 60:40:5; wherein the average molecular weight of polyethylene glycol is 2000; and the specific surface area of the second cement raw material is 450-550m 2 / kg.
[0016] Preferably, the curing process is: 3-5 parts of the first PVA fibers are uniformly mixed with 100 parts of the first cement raw material at a water-cement ratio of 0.4, poured at 25° C., and cured for 7 days to obtain a reinforced outer layer.
[0017] Preferably, the cross-linking and curing process is: 4-7 parts of the second PVA fiber are mixed with 100 parts of the second cement raw material and 2 parts of a 5wt% borax aqueous solution, and poured on the surface of the reinforced outer layer at a water-cement ratio of 0.45, the pouring temperature is 25°C, and the fiber-modified middle layer is obtained after curing for 7 days.
[0018] Preferably, the degree of polymerization of the PVA fiber is 1800-2000, and the degree of alcoholysis is 98%-99%; the degree of polymerization of the PVA resin is 200-300, and the degree of alcoholysis is 85-90%; the reinforcing agent includes silicon dioxide and polypropylene fiber; and the foaming agent is sodium dodecylbenzene sulfonate.
[0019] Preferably, the foaming process is: dissolve 100 parts of PVA resin and 2 parts of foaming agent in 300 parts of water, add 25 parts of polypropylene fiber and 5 parts of nano-silicon dioxide, heat to 50°C, stir at 1500rpm for 30 minutes, and then pour on the surface of the fiber-modified middle layer, dry at 50°C for 12 hours, cool to 25°C and dry for 48 hours to obtain a foamed inner layer.
[0020] A polyvinyl alcohol fiber reinforced cement board comprises a reinforced outer layer, a fiber modified middle layer and a foamed inner layer; wherein the thickness of the reinforced outer layer is 5 mm, the thickness of the fiber modified middle layer is 6 mm, and the thickness of the foamed inner layer is 6 mm.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The first PVA fiber prepared by copolymerization and surface modification is cured with the first cement raw material containing high-aluminum cement, sulphoaluminum cement and triphenyl phosphate to obtain a reinforced outer layer. The flame retardancy and mechanical strength of the first PVA fiber are enhanced by the copolymerization reaction of vinyl alcohol and vinyl chloride, and the fire retardant performance of the reinforced outer layer is greatly improved by the synergistic effect with triphenyl phosphate. At the same time, the rapid hardening characteristics of high-aluminum cement enable the first PVA fiber to be quickly cured after being mixed with the first cement raw material. The surface-modified PVA fiber effectively forms a hardened network with the cement, which improves the mechanical strength and weather resistance of the reinforced outer layer.
[0023] 2. The fiber-modified middle layer is prepared by cross-linking and curing the second PVA fiber modified by cross-linking and curing with the second cement raw material containing polyethylene glycol under the action of borax aqueous solution. The modified PVA fiber with a higher content can bridge and strengthen the cement body. At the same time, the modified second PVA fiber can form a cross-linked network with silicate cement under the action of borax, avoiding the problem of gradual decrease in the bonding strength between the fiber and cement, and having significant anti-aging properties under the premise of ensuring the toughness of the fiber-modified middle layer.
[0024] 3. The second PVA fiber and the second cement raw material are cross-linked and cured on the surface of the reinforced outer layer after curing for 7 days. Without affecting the basic structure and performance of the reinforced outer layer, a partially cross-linked fiber-cement network is formed between the reinforced outer layer and the fiber-modified middle layer, organically connecting the two different reinforced cement boards, effectively improving the problem of easy separation of adhesive bonding between multi-layer composite cement boards, reducing the process difficulty, and no polluting gas will be volatilized. At the same time, the organic combination of the two-layer structure can enhance the functional combination and synergy of the two-layer structure, ensuring that the reinforced cement board has both high toughness and high strength, and high weather resistance.
[0025] 4. The PVA resin, reinforcing agent and foaming agent are directly prepared on the surface of the fiber-modified middle layer through foaming treatment, which reduces the structural weight of the composite cement board. At the same time, the in-situ foaming process allows the foamed inner layer to fully fill the tiny depressions and holes on the surface of the fiber-modified middle layer to form a flat filling layer, which improves the cushioning, shock absorption and heat insulation performance of the foamed inner layer, and does not require additional bonding, effectively improving its mechanical strength.
[0026] 5. By arranging the fiber-modified middle layer between the reinforced outer layer and the foamed inner layer, the reinforced cement board prepared by the present invention has a lower difficulty in preparation process while having the functions of flame retardancy, high strength, high toughness, sound insulation and heat insulation. The fiber-modified middle layer has a high PVA content and is prepared by cross-linking and curing. It has good compatibility with the organic structure of the foamed inner layer and the inorganic structure of the reinforced outer layer, can effectively integrate the functionality of the two, and significantly improve the anti-aging property of the reinforced cement board, so that it has a longer service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the structure of the polyvinyl alcohol fiber reinforced cement board in the present invention.
[0028] In the figure, 1. reinforced outer layer; 2. fiber-modified middle layer; 3. foamed inner layer. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be clearly and completely described below through some embodiments and experimental examples. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Reference Figure 1 The present invention provides a polyvinyl alcohol fiber reinforced cement board and a manufacturing method thereof, and the technical scheme is as follows:
[0031] Example 1
[0032] 100 parts of vinyl alcohol, 30 parts of vinyl chloride and 2 parts of dioctyl phthalate are dissolved in tetrahydrofuran under a pressure of 5 atm, 1 part of azobisisobutyronitrile is added, the temperature is raised to 60°C, and the reaction is stirred at 200 rpm for 4 hours. The solution is extruded through a spinneret to obtain a copolymer fiber, which is washed with ethanol to obtain a first PVA precursor; the first PVA precursor is heated to 120°C and maintained for 3 hours, and then cooled to 25°C to obtain a first PVA fiber.
[0033] 3 parts of the first PVA fiber and 100 parts of the first cement raw material were uniformly mixed at a water-cement ratio of 0.4, poured at 25° C., and cured for 7 days to obtain a reinforced outer layer 1.
[0034] The first cement raw material includes: high alumina cement, sulphoalumina cement and triphenyl phosphate; wherein the addition ratio of high alumina cement, sulphoalumina cement and triphenyl phosphate is 30:70:1.
[0035] 100 parts of PVA fibers were soaked in water and swollen at 40°C for 2 hours to obtain swollen PVA fibers; 100 parts of swollen PVA fibers were placed in a 4wt% glutaraldehyde solution, the pH was adjusted to 3, stirred at 60°C at 300 rpm for 3.5 hours, washed and dried to obtain a second PVA fiber. The PVA fiber had a polymerization degree of 1800 and an alcoholysis degree of 98%.
[0036] 4 parts of the second PVA fiber were mixed with 100 parts of the second cement raw material and 2 parts of a 5wt% borax aqueous solution, and poured on the surface of the reinforced outer layer 1 at a water-cement ratio of 0.45 at a pouring temperature of 25°C. After curing for 7 days, a fiber-modified middle layer 2 was obtained.
[0037] The second cement raw material includes: silicate cement, sulphoaluminum cement and polyethylene glycol; wherein the addition ratio of silicate cement, sulphoaluminum cement and polyethylene glycol is 60:40:5; wherein the average molecular weight of polyethylene glycol is 2000; and the specific surface area of the second cement raw material is 450m 2 / kg.
[0038] 100 parts of PVA resin and 2 parts of sodium dodecylbenzene sulfonate are dissolved in 300 parts of water, 25 parts of polypropylene fibers and 5 parts of nano-silicon dioxide are added, the temperature is raised to 50°C, and the mixture is stirred at 1500 rpm for 30 minutes, and then poured on the surface of the fiber-modified middle layer 2. After drying at 50°C for 12 hours, the temperature is lowered to 25°C and dried for 48 hours to obtain a foamed inner layer 3.
[0039] Among them, the degree of polymerization of PVA resin is 200, and the degree of alcoholysis is 85%; the degree of polymerization of polypropylene fiber is 1500; the average particle size of nano-silica is 50nm, and the PDI is 0.1.
[0040] Embodiment 2-10 is different from Embodiment 1 in process parameters, and other process steps are the same. The relevant parameters are summarized in Table 1 and Table 2.
[0041] Examples 11-20 are different from Example 1 in process parameters, and the foaming agent is sodium fatty alcohol polyoxyethylene ether sulfate. The other process steps are the same. The relevant parameters are summarized in Table 1 and Table 2.
[0042] Table 1 Variation of process parameters in Examples 1-20 (I)
[0043] Table 2 Variation of process parameters in Examples 1-20 (II)
[0044] Comparative Example 1 The difference from Example 1 is that PVA fibers with a degree of polymerization of 1800 and a degree of alcoholysis of 98% are used instead of the first PVA fibers to participate in the curing treatment, and other process parameters are the same.
[0045] Comparative Example 2 The difference from Example 1 is that PVA fibers with a degree of polymerization of 1800 and a degree of alcoholysis of 98% are used to replace the first PVA fibers in the curing treatment after surface modification, and other process parameters are the same.
[0046] Comparative Example 3 Different from Example 1, the first PVA fiber is not subjected to surface modification treatment, and other process parameters are the same.
[0047] Comparative Example 4 The difference from Example 1 is that no triphenyl phosphate is added to the first cement raw material, and other process parameters are the same.
[0048] Comparative Example 5 The difference from Example 1 is that high alumina cement is not added to the first cement raw material, but sulphoalumina cement is used instead in equal parts, and other process parameters are the same.
[0049] Comparative Example 6 The difference from Example 5 is that no borax aqueous solution is added, and other process parameters are the same.
[0050] Comparative Example 7 The difference from Example 5 is that the cross-linking modification of the second PVA fiber is not performed, and the other process parameters are the same.
[0051] Comparative Example 8 The difference from Example 5 is that polyethylene glycol is not added to the second cement raw material, and other process parameters are the same.
[0052] Comparative Example 9 The difference from Example 5 is that the addition amount of the second PVA fiber is changed to 2 parts, and the other process parameters are the same.
[0053] Comparative Example 10 The difference from Example 10 is that the curing time of the reinforced outer layer 1 is changed to 3 days, and the other process parameters are the same.
[0054] Comparative Example 11 The difference from Example 10 is that the curing time of the reinforced outer layer 1 is changed to 14 days, and the other process parameters are the same.
[0055] Comparative Example 12 Different from Example 10, the reinforced outer layer 1 and the fiber-modified middle layer 2 are prepared separately and bonded with a polyurethane adhesive, and other process parameters are the same.
[0056] Comparative Example 13 The difference from Example 11 is that no nano-silicon dioxide is added to the reinforcing agent, and other process parameters are the same.
[0057] Comparative Example 14 The difference from Example 11 is that no polypropylene fiber is added to the reinforcing agent, and other process parameters are the same.
[0058] Comparative Example 15 Different from Example 11, the foamed inner layer 3 is prepared separately and bonded to the surface of the fiber-modified middle layer 2 with a polyurethane adhesive, and the other process parameters are the same.
[0059] Comparative Example 16 The difference from Example 15 is that the fiber-modified middle layer 2 is removed, and the foamed inner layer 3 is directly prepared on the surface of the reinforced outer layer 1, and the other process parameters are the same.
[0060] Comparative Example 17 The difference from Example 15 is that the reinforced outer layer 1 is placed between the fiber-modified middle layer 2 and the foamed inner layer 3, and the other process parameters are the same.
[0061] Comparative Example 18 The difference from Example 15 is that the foamed inner layer 3 is placed between the fiber-modified middle layer 2 and the reinforced outer layer 1, and the other process parameters are the same.
[0062] Experimental Example 1 The polyvinyl alcohol fiber reinforced cement boards prepared in Examples 1-4 and Comparative Examples 1-5 were cut into a size of 50 cm × 50 cm, and the surface of the reinforced outer layer 1 was heated with a high-temperature spray gun. The flame temperature was adjusted to 1000°C and the heating time was 5 min. The temperature of the foamed inner layer 3 of the polyvinyl alcohol fiber reinforced cement board after heating and the cracking and peeling of the surface of the reinforced outer layer 1 were recorded. The results are summarized in Table 3.
[0063] The compressive properties of the polyvinyl alcohol fiber reinforced cement boards prepared in Examples 1-4 and Comparative Examples 1-5 were tested with reference to GB / T50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", and the results are summarized in Table 3.
[0064] In order to characterize the weather resistance of reinforced cement board as exterior wall material, at 50°C and 90% humidity, the reinforced outer layer 1 of the polyvinyl alcohol fiber reinforced cement board prepared in Examples 1-4 and Comparative Examples 1-5 was sprayed with 1wt% hydrochloric acid and kept for 24 hours to test their respective compressive strengths. The results are summarized in Table 3.
[0065] Table 3 Fire resistance, compressive strength and weather resistance of cement boards prepared in Examples 1-4 and Comparative Examples 1-5
[0066] As shown in the fire resistance, compressive strength and weather resistance data of Table 3, the reinforced cement boards prepared in Examples 1-4 all have high compressive strength, and no significant cracking and peeling phenomenon occurs under short-term high-temperature flame direct baking. The temperature of the inner layer is much lower than the flame temperature, and has good fire resistance and flame retardant properties. At the same time, the compressive strength loss of the reinforced cement board after acid treatment is not large, and it has excellent weather resistance as an exterior wall material. Since Comparative Example 1 does not use PVA fibers that have been copolymerized and surface-modified with polyvinyl chloride, the fire resistance and flame retardancy are significantly reduced, and the compressive strength is also significantly lost. Comparative Example 2 performs surface modification on the uncopolymerized PVA fibers, which improves the performance of the obtained reinforced cement board, but there is still a certain performance loss compared with Examples 1-4. Comparative Example 3 uses copolymerized PVA fibers but does not perform surface modification. The bonding degree between the PVA fibers and the cement matrix is low, so while cracking occurs at high temperature, the compressive strength also decreases to a certain extent. In Comparative Example 4, due to the lack of triphenyl phosphate, the fire resistance is significantly reduced. While the reinforced outer layer 1 cracks and peels off, the temperature of the inner layer also increases significantly, and the fire resistance is greatly reduced. In Comparative Example 5, because high-alumina cement is not used, the strength of the reinforced cement board decreases, and the fire resistance decreases significantly. In summary, the flame retardancy and mechanical strength of the first PVA fiber can be significantly enhanced through the copolymerization reaction of vinyl alcohol and vinyl chloride, and the fire resistance and flame retardancy of the reinforced outer layer 1 are improved through the synergistic effect with triphenyl phosphate; further, the rapid hardening characteristics of high-alumina cement enable the first PVA fiber to be quickly cured after mixing with the first cement raw material, and the surface-modified PVA fiber effectively forms a hardened network with the cement, which improves the mechanical strength and weather resistance of the reinforced outer layer 1.
[0067] Experimental Example 2 The polyvinyl alcohol fiber reinforced cement boards prepared in Examples 5-9 and Comparative Examples 6-9 were cut into 300 mm*200 mm cement boards and subjected to fracture toughness tests. The results are summarized in Table 4.
[0068] In order to characterize the aging resistance of different cement boards, the polyvinyl alcohol fiber reinforced cement boards prepared in Examples 5-9 and Comparative Examples 6-9 were cooled to -10°C, heated to 140°C at a heating rate of 50°C / min, maintained for 3 minutes, and then cooled to -10°C again. After 50 cycles, the fracture toughness test was performed again. The results are summarized in Table 4.
[0069] Table 4 Fracture toughness and aging resistance of cement boards prepared in Examples 5-9 and Comparative Examples 6-9
[0070] As shown in the fracture toughness and aging resistance data of Table 4, Examples 5-9 have relatively stable fracture toughness, and after the cooling-heating aging test, the fracture toughness decays less, and has significant aging resistance. Comparative Example 6 does not add borax aqueous solution, and the in-situ crosslinking and curing process of the second PVA fiber and the second cement raw material is difficult to carry out. In the ordinary cement curing process, it is difficult to form a composite crosslinking network, resulting in a significant reduction in the toughness of the obtained cement board. Comparative Example 7 does not crosslink and modify the PVA fiber, resulting in a decrease in the toughness of the formed fiber-modified intermediate layer 2, and the combination of the PVA fiber and cement is greatly affected by the environment. After the aging test, the bonding strength decreases significantly, resulting in a significant decrease in toughness. In Comparative Example 8, polyethylene glycol is not added, and the compatibility of the PVA fiber and the cement matrix is reduced. Therefore, the bonding strength decreases significantly after the aging test, which also leads to a significant decrease in toughness. Comparative Example 9 reduces the amount of the second PVA fiber, reduces the density of the reinforcing network, and reduces the toughness of the reinforced cement board to a certain extent. In summary, the fiber-modified intermediate layer 2 prepared by cross-linking and curing the cross-linked modified second PVA fiber and the second cement raw material containing polyethylene glycol under the action of borax aqueous solution has significantly high toughness. At the same time, because the modified high-content second PVA fiber and silicate cement form a three-dimensional cross-linked network, the problem of gradual decrease in the bonding strength between the fiber and cement is avoided, and it has significant anti-aging properties while ensuring the toughness of the fiber-modified intermediate layer 2.
[0071] Experimental Example 3 Referring to Experimental Example 1 and Experimental Example 2, the compressive strength, compressive strength after acid treatment, fracture toughness and fracture toughness after aging treatment of the reinforced cement boards prepared in Example 10 and Comparative Examples 10-12 were tested, and the results are summarized in Table 5.
[0072] Table 5 Compressive strength, compressive strength after acid treatment, fracture toughness and fracture toughness after aging treatment of cement boards prepared in Example 10 and Comparative Examples 10-12
[0073] As shown in the relevant data of Table 5, the cement boards prepared in Example 10 and Examples 1-9 have similar compressive strength and fracture toughness, and their weather resistance and aging resistance are almost the same. In Comparative Example 10, since the curing time of the reinforced outer layer 1 is too short, the curing process of the reinforced outer layer 1 is interfered with during the preparation of the fiber-modified intermediate layer 2, resulting in more structural defects, which is reflected in the cement board product as a significant decrease in fracture toughness and compressive strength. In Comparative Example 11, since the curing of the reinforced outer layer 1 has been completely completed, it is difficult to form a partially cross-linked fiber-cement network between the two layers during the preparation of the fiber-modified intermediate layer 2, resulting in a decrease in its toughness and aging resistance, but a slight increase in compressive strength. In Comparative Example 12, the reinforced outer layer 1 and the fiber-modified intermediate layer 2 are not combined through the cross-linking and curing process, but are directly bonded using an adhesive, so the composite effect of the two layers is significantly reduced, and all the properties of the cement board are greatly lost. In summary, cross-linking and curing the surface of the reinforced outer layer 1 after 7 days of curing to prepare the fiber-modified middle layer 2 effectively forms a partially cross-linked fiber-cement network between the two layers, organically connecting the two different reinforced cement boards, improving the composite effect of the two layers of board with different structures, and reducing the process difficulty, ensuring that the reinforced cement board has high toughness, high strength and high weather resistance.
[0074] Experimental Example 4 With reference to Experimental Example 1 and Experimental Example 2, the compressive strength and fracture toughness of the reinforced cement boards prepared in Examples 11-14 and Comparative Examples 13-15 were tested, and the results are summarized in Table 6.
[0075] The thermal conductivity of the reinforced cement boards prepared in Examples 11-14 and Comparative Examples 13-15 was measured, and the results are summarized in Table 6.
[0076] Table 6 Thermal conductivity, compressive strength and fracture toughness of cement boards prepared in Examples 11-14 and Comparative Examples 13-15
[0077] As shown in the thermal conductivity, compressive strength and fracture toughness data of Table 6, Examples 11-14 use sodium sulfate of fatty alcohol polyoxyethylene ether as a foaming agent, and the strength of the foam layer is reduced, but the fracture toughness and compressive strength of the reinforced cement board as a whole are still at a better level, and the thermal conductivity is low, which means that its thermal insulation is good. For Comparative Example 13, the lack of nano-silicon dioxide significantly reduces the strength of the foam layer, resulting in a decrease in the fracture toughness and compressive strength of the reinforced cement board as a whole, but has little effect on the thermal conductivity. Due to the lack of polypropylene fiber in Comparative Example 14, the foam structure of the foamed inner layer 3 is unstable, resulting in a decrease in the thermal insulation performance of the foamed layer, that is, the thermal conductivity increases by a large margin, but has little effect on the fracture toughness and compressive strength. For Comparative Example 15, the foamed inner layer 3 is not prepared in situ on the surface of the fiber-modified intermediate layer 2, resulting in the foaming process being unable to fully fill the tiny depressions and holes on the surface of the intermediate layer, so that the mechanical strength of the reinforced cement board is slightly reduced and the thermal insulation performance is slightly reduced. In summary, the synergistic effect of the two reinforcing agents and the in-situ foaming process make the foamed inner layer 3 and the fiber-modified middle layer 2 more tightly bonded, and the filling layer more flat, which effectively improves the cushioning, shock absorption and heat insulation properties of the foamed inner layer, and does not require additional bonding, effectively improving its mechanical strength.
[0078] Experimental Example 5 Referring to Experimental Example 2, the fracture toughness and aging resistance of the reinforced cement boards prepared in Examples 15-20 and Comparative Examples 16-18 were tested, and the results are summarized in Table 7.
[0079] The sound absorption coefficient of the reinforced cement boards prepared in Examples 15-20 and Comparative Examples 16-18 was tested using the standing wave tube method, and the results are summarized in Table 7.
[0080] Table 7 Fracture toughness, aging resistance and sound absorption coefficient of cement boards prepared in Examples 15-20 and Comparative Examples 16-18
[0081] As shown in the fracture toughness, aging resistance and sound absorption coefficient data of Table 7, Examples 15-20 have no significant difference from Examples 1-14 in terms of fracture toughness and aging resistance, and have a higher sound absorption coefficient, and have the sound insulation performance required by exterior wall materials. Comparative Example 16 lacks the fiber-modified intermediate layer 2, so the combination of the reinforced outer layer 1 and the foamed inner layer 3 is not tight, and lacks the strongest layer of toughness, resulting in a significant reduction in the fracture toughness of the cement board and a significant attenuation of the sound absorption coefficient. Comparative Examples 17 and 18 swap the order of the three functional layers, but whether the reinforced outer layer 1 is placed in the center or the foamed inner layer 3 is placed in the center, its fracture toughness and aging resistance are far inferior to the structure with the fiber-modified intermediate layer 2 in the center, and the sound absorption coefficient is also significantly reduced. In summary, arranging the fiber-modified intermediate layer 2 between the reinforced outer layer 1 and the foamed inner layer 3 can effectively combine the different functions of the three-layer structure and give play to the advantages of the three in different aspects. That is, the fiber-modified middle layer has a high PVA content and is prepared through cross-linking and curing. It has good compatibility with the organic structure of the foamed inner layer and the inorganic structure of the reinforced outer layer. It can effectively combine the functionality of the two, significantly improve the aging resistance of the reinforced cement board, and ensure the normal performance of its high strength, high toughness, sound insulation and heat insulation functions.
[0082] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for manufacturing a polyvinyl alcohol fiber reinforced cement board, characterized in that: The production method is as follows: Preliminarily mixing the first PVA fiber and the first cement raw material, and curing them in a mold to obtain a reinforced outer layer (1); Wherein, the first PVA fiber is obtained by copolymerization and surface modification; The second PVA fiber and the second cement raw material are stirred and mixed, and after the surface of the reinforced outer layer (1) is cross-linked and cured, a fiber-modified middle layer (2) is obtained; Wherein, the second PVA fiber is obtained by cross-linking modification; The PVA resin is mixed with a reinforcing agent and a foaming agent, and then foaming treatment is performed on the surface of the fiber-modified intermediate layer (2) to obtain a foamed inner layer (3), thereby producing the polyvinyl alcohol fiber reinforced cement board.
2. The method for manufacturing a polyvinyl alcohol fiber reinforced cement board according to claim 1, characterized in that: The first cement raw material includes: high alumina cement, sulphoaluminum cement and triphenyl phosphate; wherein the addition ratio of the high alumina cement, the sulphoaluminum cement and the triphenyl phosphate is 30:70:1; the second cement raw material includes: silicate cement, sulphoaluminum cement and polyethylene glycol; wherein the addition ratio of the silicate cement, the sulphoaluminum cement and the polyethylene glycol is 60:40:5; wherein the average molecular weight of the polyethylene glycol is 2000; the specific surface area of the second cement raw material is 450-550m 2 / kg.
3. The method for manufacturing a polyvinyl alcohol fiber reinforced cement board according to claim 1, characterized in that: The process of the copolymerization reaction is as follows: 100 parts of vinyl alcohol, 30 parts of vinyl chloride and 2 parts of dioctyl phthalate are dissolved in tetrahydrofuran at a pressure of 5 atm, 1 part of azobisisobutyronitrile is added, the temperature is raised to 60-80°C, and the mixture is stirred at a speed of 200 rpm for reaction for 4-5 hours, the solution is extruded through a spinneret to obtain copolymer fibers, and the copolymer fibers are washed with ethanol to obtain a first PVA precursor; the process of the surface modification is as follows: the first PVA precursor is heated to 120°C and maintained for 3 hours, and the first PVA fiber is obtained after being cooled to 25°C.
4. The method for manufacturing a polyvinyl alcohol fiber reinforced cement board according to claim 1, characterized in that: The curing process is as follows: 3-5 parts of the first PVA fibers are uniformly mixed with 100 parts of the first cement raw material at a water-cement ratio of 0.4, poured at 25° C., and cured for 7 days to obtain the reinforced outer layer (1).
5. The method for manufacturing a polyvinyl alcohol fiber reinforced cement board according to claim 1, characterized in that: The cross-linking modification process is as follows: immersing 100 parts of PVA fibers in water, and swelling them at 40°C for 2 hours to obtain swollen PVA fibers; placing 100 parts of the swollen PVA fibers in a 4wt% glutaraldehyde solution, adjusting the pH to 3-4, stirring at 60°C at a speed of 300rpm for 3.5 hours, and washing and drying to obtain the second PVA fibers; wherein the PVA fibers have a degree of polymerization of 1800-2000 and a degree of alcoholysis of 98%-99%.
6. The method for manufacturing a polyvinyl alcohol fiber reinforced cement board according to claim 1, characterized in that: The cross-linking and curing process is as follows: 4-7 parts of the second PVA fibers are mixed with 100 parts of the second cement raw material and 2 parts of a 5wt% borax aqueous solution, and poured onto the surface of the reinforced outer layer (1) at a water-cement ratio of 0.45 at a pouring temperature of 25°C. After curing for 7 days, the fiber-modified intermediate layer (2) is obtained.
7. The method for manufacturing a polyvinyl alcohol fiber reinforced cement board according to claim 1, characterized in that: The PVA resin has a polymerization degree of 200-300 and a degree of alcoholysis of 85-90%; the reinforcing agent includes nano-silica and polypropylene fibers, and the foaming agent is sodium dodecylbenzene sulfonate or sodium polyoxyethylene fatty alcohol ether sulfate; the foaming process is as follows: 100 parts of the PVA resin and 2 parts of the foaming agent are dissolved in 300 parts of water, 25 parts of the polypropylene fibers and 5 parts of the nano-silica are added, the temperature is raised to 50° C., the mixture is stirred at a speed of 1500 rpm for 30 minutes, and then poured onto the surface of the fiber-modified intermediate layer (2), dried at 50° C. for 12 hours, and then cooled to 25° C. and dried for 48 hours to obtain the foamed inner layer (3).
8. A polyvinyl alcohol fiber reinforced cement board, characterized in that: The polyvinyl alcohol fiber reinforced cement board is manufactured by the manufacturing method according to any one of claims 1 to 7; the polyvinyl alcohol fiber reinforced cement board comprises: a reinforced outer layer (1), a fiber-modified middle layer (2) and a foamed inner layer (3); wherein the thickness of the reinforced outer layer (1) is 5 mm, the thickness of the fiber-modified middle layer (2) is 6 mm, and the thickness of the foamed inner layer (3) is 6 mm; the fiber-modified middle layer (2) is located between the reinforced outer layer (1) and the foamed inner layer (3).
Citation Information
Patent Citations
A method for preparing composite plant fiber cement board
CN112390597B
A fiber cement board and its preparation method
CN114230263B
Negative carbon fiber cement board and preparation method thereof
CN115403337B
Lightweight cement panel
CN102409840A
Fiber-reinforced cement lightweight insulating FLIC board and preparation method thereof
CN103723973A